Qur’anic Exegesis for Commoners: A Thematic Sketch of Non-Academic Tafsīr Works in Indonesia - Mu'ammar Zayn Qadafy (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2019)
This article deals with two scholarly tafsīr books circulating throughout modern Indonesia: Husein Qadri’s (1906-1966) “Senjata Mukmin” (The Weapons of the Believers) and Agus Purwanto’s (b. 1964) “Nalar Ayat-Ayat Semesta” (Reasoning of the Verses of the Universe). Qadri, representing his position as Muslim scholar, and Purwanto, as Muslim intellectual, contribute to the shaping of lay exegesis in their country. I conclude that although the two works are completely different with regard to genre, methodology and style, both are concerned with attracting the attention of lay readers and, accordingly, endeavor to present their information in a comprehensible and accessible manner. In term of content, the two books limit their discussion to the apparent (ẓāhir) meaning of the Qur’an, an understanding that depends on a reader’s knowledge of Arabic; one might call it an immediate understanding of the text. Their works also maintain the primacy of Arabic over the Indonesian language.